2017
DOI: 10.1001/jamafacial.2017.0172
|View full text |Cite
|
Sign up to set email alerts
|

Role of Algorithm-Based Levator Aponeurectomy in Small-Incision External Ptosis Surgery for Involutional Ptosis

Abstract: IMPORTANCE External surgical treatment of involutional ptosis with normal levator function is challenging owing to lack of an established algorithm. Developing an algorithm-based technique could improve postoperative results while limiting intraoperative inefficiencies. OBJECTIVE To investigate the postoperative success of an algorithmic external levator aponeurosis resection technique for aponeurotic ptosis with good levator function. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort study included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…We congratulate the authors on their work; however, some aspects should be underlined in their study. 1 First, the columellar suture proposed by the authors seems very similar to the one reported by Daley 2 in 1944 and later described by Aufricht 3 as "submerged" suture in 1969. In the Daley-Aufricht technique, the suture is introduced through the base of the columella to emerge in the middle of the columellar base where the philtrum begins.…”
Section: Suturing Technique For the Correction Of The Obtuse Nasolabi...supporting
confidence: 64%
See 4 more Smart Citations
“…We congratulate the authors on their work; however, some aspects should be underlined in their study. 1 First, the columellar suture proposed by the authors seems very similar to the one reported by Daley 2 in 1944 and later described by Aufricht 3 as "submerged" suture in 1969. In the Daley-Aufricht technique, the suture is introduced through the base of the columella to emerge in the middle of the columellar base where the philtrum begins.…”
Section: Suturing Technique For the Correction Of The Obtuse Nasolabi...supporting
confidence: 64%
“…5 Alessandro Innocenti, MD Serena Ghezzi, MD Marco Innocenti, MD In Reply We thank Innocenti et al for their comment on our article. 1 Although we do agree that long-term follow-up is necessary to establish the longevity of each procedure, there is no consensus in the literature regarding the necessary minimum follow-up time for upper-eyelid ptosis repair procedures. Several prior published reports of ptosis repair techniques have had similar or less follow-up time compared with our study.…”
Section: Considerations On the Role Of Algorithm-based Levator Aponeu...mentioning
confidence: 95%
See 3 more Smart Citations